2004
DOI: 10.1128/cdli.11.4.651-657.2004
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Linked Immunosorbent Assays Using Recombinant Envelope Protein Expressed in COS-1 and Drosophila S2 Cells for Detection of West Nile Virus Immunoglobulin M in Serum or Cerebrospinal Fluid

Abstract: Humans infected with West Nile virus (WNV) develop immunoglobulin M (IgM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Most WNV IgM assays utilize recombinant premembrane/envelope (preM/E) protein (Davis et al, 2001). These assays exhibit excellent sensitivity for identifying individuals recently exposed to WNV (Hogrefe et al, 2004;Muerhoff et al, 2004;Holmes et al, 2005;Tilley et al, 2005;Rawlins et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Most WNV IgM assays utilize recombinant premembrane/envelope (preM/E) protein (Davis et al, 2001). These assays exhibit excellent sensitivity for identifying individuals recently exposed to WNV (Hogrefe et al, 2004;Muerhoff et al, 2004;Holmes et al, 2005;Tilley et al, 2005;Rawlins et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, several ELISAs have been developed using recombinant viral proteins, mainly the envelope E protein or parts of it, because this protein is highly exposed to the host immune system and bears most of the neutralizing epitopes described [206] . These recombinant antigens have been expressed in a variety of systems, including bacteria [207] , mammalian cells [208,209] , insect cells [209][210][211] , and larvae [211] . Other formats, such as microsphere particles in conjunction with fluorescent labelled antibodies and lateral-flow assays have also been recently assayed [53] .…”
Section: Antibodymentioning
confidence: 99%
“…There are several examples of the use of recombinant E proteins of WNV to develop diagnostic tests that are based on the indirect ELISA format (3,13,21,35). However, in a preliminary study using a competitive ELISA format, we found that WNV serum-neutralizing antibodies in most equine sera did not inhibit 5E8 binding to recombinant E protein expressed in Escherichia coli, perhaps due to conformational alterations in critical antigenic structures in the recombinant E protein.…”
Section: Discussionmentioning
confidence: 91%